Analisis Regenerasi Guru Berdasarkan Kelompok Umur di Maluku, Bali, Bangka Belitung, dan Gorontalo - Bima Ardiansyah Haz; Dimas Febrian; Rizki Syafrizal (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
This research discusses the age distribution of school principals and teachers and the problems that arise related to age imbalance in the teaching staff. This imbalance can affect the regeneration and quality of education, especially if the majority of teachers are approaching retirement age. Each age group has its own challenges and advantages in adapting to technology and curriculum changes. This research uses secondary data from educational statistical reports and government agency databases. The aim is to analyze age distribution, identify regeneration needs, and provide policy recommendations regarding the recruitment and training of teaching staff.